O romance policial de Rubem Fonseca - Marinho, Maria de Fátima (2024)
It was from the 19th century onwards that the interest in reading texts involving detective puzzles began to emerge and a paradigm was quickly established which, with slight variations, has remained almost the same until today. The novels published in recent decades, however, have tended to redefine the code and de-centre these characters, who no longer have the same level of gratu-itous eccentricity (as Poirot or Sherlock Holmes), but rather a positioning derived from the trivialisation of police/detectives, who are placed at the level of the ordinary, problematic citizen, with small habits that deviate from a rigid, moralising norm. Rubem Fonseca's novels are in this vein, with policemen, lawyers and criminals playing off against each other, surrounded by corruption of all kinds and relationships far removed from those that could be considered to belong to a privileged moral space. In this short essay, we will focus on Rubem Fonseca's crime-themed novels.